Awareness to the islamic social reporting (ISR) disclosure: A case study in companies listed in Jakarta islamic index (JII) - Haryono Haryono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to analyze the disclosure of corporate social responsibility in sharia and its determinants. The data used is the annual report of 22 companies registered with JII from 2015 - 2018. The research method used is content analysis. The findings of this study that all explanatory variables which include liquidity, profitability, type of industry, firm size and firm age significantly affect the disclosure of ISR. Liquidity and profitability have a significant negative effect on ISR disclosure. Industry type, company size, and company age have a significant positive effect on ISR disclosure. The findings of the first two variables indicate that companies tend to disclose ISR when experiencing financial problems.